2016
DOI: 10.3389/fmicb.2016.01981
|View full text |Cite
|
Sign up to set email alerts
|

Outer Membrane Vesicles and Soluble Factors Released by Probiotic Escherichia coli Nissle 1917 and Commensal ECOR63 Enhance Barrier Function by Regulating Expression of Tight Junction Proteins in Intestinal Epithelial Cells

Abstract: The gastrointestinal epithelial layer forms a physical and biochemical barrier that maintains the segregation between host and intestinal microbiota. The integrity of this barrier is critical in maintaining homeostasis in the body and its dysfunction is linked to a variety of illnesses, especially inflammatory bowel disease. Gut microbes, and particularly probiotic bacteria, modulate the barrier integrity by reducing gut permeability and reinforcing tight junctions. Probiotic Escherichia coli Nissle 1917 (EcN)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
143
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(151 citation statements)
references
References 52 publications
5
143
1
2
Order By: Relevance
“…Consequently, rapid promotion of mucosal healing has been considered crucial in the management of intestinal inflammation (Dave and Loftus, 2012). Under conditions of intact epithelial barrier EcN OMVs (100 μg/ml) upregulate expression of claudin-14 and ZO-1 in T-84 and Caco-2 monolayers (Alvarez et al, 2016). However, oral administration of EcN OMVs does not prevent DSS-induced downregulation of ZO-1 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, rapid promotion of mucosal healing has been considered crucial in the management of intestinal inflammation (Dave and Loftus, 2012). Under conditions of intact epithelial barrier EcN OMVs (100 μg/ml) upregulate expression of claudin-14 and ZO-1 in T-84 and Caco-2 monolayers (Alvarez et al, 2016). However, oral administration of EcN OMVs does not prevent DSS-induced downregulation of ZO-1 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…The EVs of most bacteria are obtained by blistering the outer membrane and ultimately pinching off the bacterial cytoderm, so they are referred to as outer membrane vesicles (OMVs). Studies have shown that OMVs secreted by E. coli ECOR63 and EcN can upregulate tight junction proteins such as claudin-14 and ZO-1 [75,76]. Probiotic EcN derived OMVs can also induce IL-22 expression in colonic explants, thereby preventing allergens and pathogenic microorganisms from entering the systemic circulation [75].…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…In 2016, Alvarez et al illustrated that EVs from both EcN and ECOR63 have a strengthening ability based on TcpC. EVs isolated from these probiotics can promote the upregulation of ZO-1 and claudin-14 and downregulation of claudin-2, thus helping the reinforcement of the epithelial barrier, while the specific mechanism has not yet been illustrated [53]. EVs from Bacteroides thetaiotaomicron (BtMinpp) may protect enzymes from degradation by gastrointestinal proteases and promote intracellular Ca (2+) signaling, thus maintaining the physiological responses of the digestive system [54].…”
Section: Evs In Ibdmentioning
confidence: 99%